Pengaruh Penerapan Metode Think Pair Share Disertai dengan Game Truth or Dare Terhadap Hasil Belajar Siswa - Mela Cahya Putri; Friyatmi Friyatmi (Universitas Negeri Padang, 2024)
The aimed of this study is to ascertain how the truth-or-dare game and the think-pair-share method affect the learning outcomes of students at SMAN 1 Kec. New Koto Base. This study used a randomized control group pretest-posttest design and is a quantitative experimental research design. Purposive sampling was used to choose the research sample. The class X IPS 1 and X IPS 2 sample was selected. A test of the learning outcomes of the students was the research tool used. The t test was used in this study to assess the hypothesis. plans for study of several kinds. The study's findings indicate that when students play the truth-or-dare game in addition to the think-pair-share technique, their learning outcomes alter.